2022
DOI: 10.3233/jad-220155
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Caregiver Management Styles to the Discrepancy Between Reported and Observed Task Performance in People with Dementia

Abstract: Background: The identification and understanding of the discrepancy between caregivers’ reports of people with dementia’s (PwD) performance of activities of daily living (ADLs) and observed performance, could clarify what kind of support a PwD effectively needs when completing tasks. Strategies used by caregivers have not been included in the investigation of this discrepancy. Objective: To (1) investigate if caregivers’ report of PwD’s ADL performance are consistent with PwD’s observed performance; (2) explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…36,40 A possible reason why caregivers rate iADL difficulties over time as increasing more markedly relative to cognitive decline and selfrated iADL may relate to the effects of increasing adjustment to their caregiver role, 41 that is, evolution of coping style and coping strategies, increasing caregiving experience, and changes in the types of care provided. 40,42,43 As caregivers become accustomed to the demands of caregiving they might be more able to recognize or more willing to acknowledge difficulties. This might make it more likely for caregivers to rate iADL as more impaired than self-ratings made by people with dementia.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…36,40 A possible reason why caregivers rate iADL difficulties over time as increasing more markedly relative to cognitive decline and selfrated iADL may relate to the effects of increasing adjustment to their caregiver role, 41 that is, evolution of coping style and coping strategies, increasing caregiving experience, and changes in the types of care provided. 40,42,43 As caregivers become accustomed to the demands of caregiving they might be more able to recognize or more willing to acknowledge difficulties. This might make it more likely for caregivers to rate iADL as more impaired than self-ratings made by people with dementia.…”
Section: Discussionmentioning
confidence: 99%
“…This could comprise qualitative interviews at regular intervals and a brief objective measure of iADL with corresponding appraisal ratings; this would allow for a deeper understanding of how caregivers and people with dementia perceive iADL difficulties as well as help understand changes in caregiver adjustment, coping strategies, and stress/burden. This is especially salient as coping strategies, adjustment, and burden influence how informants rate iADL difficulties, 10,40,[45][46][47] and higher perceived stress is often associated with more perceived iADL difficulties. 3,10,15,17,19 How ratings accord with actual abilities is unknown, though a previous study found that people with mild-to-moderate dementia were able to rate performance on iADL tasks more accurately than corresponding ratings by their caregivers, particularly with tasks that do not largely rely on intact memory ability; for example, telling the time, or identifying medication.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations